Penyelarasan Kurikulum Jurusan Pendidikan Teknik Otomotif FT UNYBerbasis Kerangka Kualifikasi Nasional Indonesia - Zainal Arifin; Martubi Martubi; Kir Haryana; Moch. Solikin; Ibnu Siswanto (Jurnal Pendidikan Teknologi dan Kejuruan, 2014)
The objectives of this study were (1) to identify and analyse the competencies required by the graduates of the Department of Automotive Engineering Education, Faculty of Engineering, Yogyakarta State University (YSU) in the workforce in accordance with the Indonesian National Qualification Framework (2) to develop the curriculum design that meets the needs of the workforce and the Indonesian National Qualification Framework, and (3) to develop the curriculum and the distribution of each competency in each course held at the Department. This study consists of the following stages: the evaluation of the existing curriculum through literature studies and workshops as well as the development of a new curriculum design. The workshop was conducted by presenting two practitioners from industry and 5 education practitioners and lecturers from the Department of Automotive Engineering Education, Faculty of Engineering, YSU. The results of the study were (1) the identification and the analysis results of the required competencies (2) the draft of the curriculum, and (3) the curriculum networking and the distribution of each competency in each course.